Towards a Typology of Literary Translation: Drama Translation Science - Zuber-Skerritt, Ortrun (Meta, 1988)
AbstractBased on the ideas of my two edited books The Languages of Theatre (Problems in the Translation and Transposition of Drama) and Page to Stage (Theatre as Translation), this paper attempts to arrive at a typology of translation which deals with both the translation of drama from one language and culture into another and with the various aspects of transposing the dramatic script on to the stage or, vice versa, the creation of drama through processes of theatre production. The focus is on those aspects of drama translation which are different from other forms of literary translation, e.g. on problems of semiotics (i.e. translating non-verbal signs in drama). The paper concludes with recommendations for future developments in drama translation research, including the production process, Le. the transposition from the written (translated) drama to the performed work of art, and the conceptualisation of the production process.